Appropriateness of Antibiotic Utilization in Hospitalized Post-Surgery Patients - Nasution, Azizah; Fashilah, Noor; Nugraha, Sony Eka (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
Abstract. One of the most common health problems related to surgery is infection which needs treatment with antibiotics. Inappropriate use of antibiotics results in many problems including microbial resistance, interference of the required clinical outcomes, increasing side effects of the provided antibiotics and health resources utilization, causing toxic effects to the body organs, and even death. This study aimed to evaluate the appropriateness of antibiotic utilization on post-surgery patients admitted to Haji Adam Malik (HAM) Hospital, Medan, Indonesia. This three-month prospective descriptive study was conducted to evaluate the appropriateness of antibiotic utilization based on Gyssens method categorized into appropriate and inappropriate (in terms of dose, interval, route, too long provision, too short provision, less effective, toxicity, price, and the spectrum), and trustable literatures on post-surgery patients assessed from their medical records (n=31) in HAM Hospital Medan. Most (54.8%) of the patients were females. The study proved that 23 (74.2%) of the patients received appropriate/rational antibiotic therapy and 8 (25.8%) of them received inappropriate antibiotic therapy consisted of problems with: inappropriate dose, 13%; too long duration, 3.2%); too short duration, 29%. More than a quarter of the patients received inappropriate dosages of antibiotics.